The electrical engineering handbook - Dorf, Richard C. (CRC Press, 1993)
A comprehensive source of electrical engineering information, this text features a complete section devoted to key mathematical formulae, concepts, definitions and derivatives. It also provides complete descriptions of select US and international professional and academic societies.